First report from Indonesia, phytochemical composition of essential oils from leaves and fruits of Zanthoxylum avicennae (Lam.) DC. - Putri Sri Andila; I Putu Agus Hendra Wibawa; I Gede Turta; Deden Fardenan (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2018)
Zanthoxylum avicennae (Lam.) DC. [Karangean] is a widely distributed plant in Southeast Asia and has potential in the pharmaceutical and food flavour industry with fruits and leaves rich in essential oils. The plant materials of Z. avicennae (Lam.) DC. [Karangean] were a plant collection at Bali Botanical Garden which collected from West Nusa Tenggara, on June 15th 1993. The essential oils were extracted by hydrodistillation from fresh fruits and leaves of Z. avicennae and the phytochemical composition were analysed by Gas Chromatography-Mass Spectrometry (GC-MS). The yields of essential oils were 2.75% from fruit oil and 1% from leaf oil. Respectively, a total of 41 compounds were identified from the fruit oil and 11 compounds from the leaf oil representing 91.1% and 99.81% of the total oils composition. The major compounds of the fruit oil were 1.8-cineol (12.34%), 1-para-menthen-8-yl acetate (6.24%), l-Limonene (6.09%), Cyclopropane (5.06%), Hexane (3.84%), 3-Methyl-2-(2-methyl-2-butenyl)-furan (3,74%) and predominant compouns of the leaf oil were Estragol (87.13%), 1.8-cineol (4.28%), Trans-Anethole (3.51%), Myrtenyl Acetate (0.65%), isopiperitenone (0.62%). The highest contents of these essential oils were monoterpene and sesquiterpene and these componentshad desirable properties for use in industrial companies. Therefore, the essential oils of Z. avicennae [Karangean] from West Nusa Tenggara contained chemical compositions which had potential to be developed for various human needs.